The Parent Company’s Liability for the Fictitious Nature of the Subsidiary Company. - Murtada Salam Hussein (Thi Qar Arts Journal, 2025)
The expansion of multinational corporations’ activities has witnessed significant development recently through the establishment of subsidiaries in various countries. However, the parent company sometimes resorts to collusion with a local partner in order to circumvent legal provisions by creating a fictitious arrangement and entering into contracts with the partner that differ from those officially documented with the authorities. This fictitious nature of the arrangement has negative repercussions on the national economy and on other stakeholders, such as shareholders. Therefore, we found it necessary to conduct a study that thoroughly examines all aspects related to the fictitious nature of corporate contracts. This study aims to propose solutions to address this issue and to clarify the legal framework that should be in place to enhance oversight of multinational corporations and prevent them from circumventing legal provisions. It also seeks to identify legal mechanisms that can assist creditors of subsidiary companies in holding the parent company accountable and recovering their debts, especially when the subsidiary is established as a sham entity.